Development of Logic Based Learning Evaluation Instruments - Kharisma Kusumaningtyas (Journal of Global Pharma Technology, 2020)
Objective: Logical models are methods for conveying ideas that describe and share the understanding of the interrelationships among elements to operate a program or change effort. The study aimed to compile the development of a logic-based clinical learning practice instrument. Method: This research used an action research design. Sixteen participants joined the Focus Group Discussion (FGD) consisting of Head of Study Program, Academic Coordinator, Practice Division staffs, and Lecturer Representatives from 4 Midwifery Study Program of a university in Indonesia. The FGD was conducted in 2 stages. The analysis used descriptive and inferential analysis. Result: The results obtained clinical practice learning evaluation instruments based on logic models. The results of the validity test with Pearson's product-moment correlation show r = 0.576 and the value of r for each question > r table, so it can be concluded that instruments valid and reliable.  Discussion: Instrument of clinical practice learning program based on logic models in the Midwifery Department consists of context, input, activity, output, and outcomes. The instrument can assess the process of implementing clinical practice learning.Keywords: Learning, Practice, Logic model, Clinical.